2013
DOI: 10.2478/hukin-2013-0053
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Levels of Vitamin D and Bone Turnover Markers After the Summer and Winter Periods in Polish Professional Soccer Players

Abstract: Vitamin D is synthesised in the skin during exposure to sunlight. The fundamental roles of vitamin D are the regulation of calcium and phosphate metabolism and bone mineralisation. Low vitamin D levels in athletes may adversely affect their exercise capabilities. The aim of our study was to investigate changes in serum levels of 25(OH)D3, calcium and bone turnover markers in football players in two training periods differing in the exposure to sunlight (after the summer period and after the winter period). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 26 publications
10
48
0
4
Order By: Relevance
“…This finding was unanticipated by the authors since they expected vitamin D levels to increase or at least to remain constant due to the adequate daily exposure to UVB during the whole study. Further support is coming from two recent studies on soccer players [43], [48]. The authors observed much lower vitamin D levels (30,82±9,04 [42], 32,83±6,64 [48]) and insufficiency values (83% <30 ng/ml [42], 65% <30 ng/ml [48]) during periods of training, compared to the ones we obtained after the six-week detraining period (45,67±13,70; 4,47<30 ng/ml).…”
Section: Discussionsupporting
confidence: 55%
“…This finding was unanticipated by the authors since they expected vitamin D levels to increase or at least to remain constant due to the adequate daily exposure to UVB during the whole study. Further support is coming from two recent studies on soccer players [43], [48]. The authors observed much lower vitamin D levels (30,82±9,04 [42], 32,83±6,64 [48]) and insufficiency values (83% <30 ng/ml [42], 65% <30 ng/ml [48]) during periods of training, compared to the ones we obtained after the six-week detraining period (45,67±13,70; 4,47<30 ng/ml).…”
Section: Discussionsupporting
confidence: 55%
“…Similar variations have been reported for athletes. In soccer players, the levels of 25(OH)D3 are normal in 50 % of the athletes, while this number drops to 16.7 % in winter [32]. A study performed in a high latitude (Laramie, WY 41.3°N) revealed vitamin D insufficiency of 63 % in winter compared to only 12 % in autumn and 20 % in spring in both indoor and outdoor athletes [38].…”
Section: Seasonal Variation Of Vitamin D Levelsmentioning
confidence: 99%
“…Koundourakis et al [28] showed that professional Greek soccer players' training at a latitude of 35.9°N had insufficient vitamin D levels, while nearly identical levels were reported in American national football league players [29], in elite gymnasts in Australia [30], and in young Hawaiian skateboarders [31] and a variety of other athletes worldwide [32][33][34][35]. These findings were observed irrespective of sun exposure.…”
Section: A Critical Evaluation Of Vitamin D -Basic Overviewmentioning
confidence: 99%
“…In soccer players, the levels of serum vitamin D are "normal" in 50% of athletes during summer, whereas it drops to 16% in winter. 105 A study performed in a high latitude area (Laramie, WY 41.3°N) revealed that the prevalence of "low" vitamin D was about 63% in winter compared to only 12% in autumn and 20% in spring in both indoor and outdoor athletes. 104 Similar findings have been reported in a study conducted at higher latitudes (Ellensburg, WA 46.9°N) using exclusively outdoor athletes.…”
Section: Geographical Latitude and Insolation On Exercise Performancementioning
confidence: 99%